MODL-02. TARGETING REPLICATION STRESS IN PEDIATRIC BRAIN TUMORS. (4th December 2020) - Krausert, Sonja; Lambo, Sander; Mack, Norman; Schwalm, Benjamin; Pfister, Stefan; Kool, Marcel
Abstract: Pediatric brain tumors harboring amplifications or high overexpression of MYC -/ MYCN are often associated with poor outcome. High MYC(N ) expression in these tumors leads to increased transcription, which can be in conflict with DNA replication and subsequently can cause replication stress, R-loops and DNA damage. We hypothesize that high MYC(N ) expression makes them vulnerable to DNA damage response inhibitors (DDRi) and even more vulnerable to combinations of DDRi and chemotherapeutics. To test this hypothesis we performed in vitro drug experiments using Group 3 medulloblastoma (MB) and ETMR cell lines. IC50-values were evaluated of topoisomerase inhibitor Irinotecan (SN-38) and Pamiparib (BGB-290), a brain-penetrant PARP-inhibitor, in monotherapy. All cell lines were sensitive for SN-38 and showed IC50-values in the low nM-range but PARP-inhibitors were ineffective. However, a significant decrease in IC50 can be observed when SN-38 and Pamiparib are used in combination. For in vivo treatments, we injected NSG mice with luciferase labelled patient-derived xenograft- (PDX-) cells of various models (MB Group 3, MB SHH, ETMR, RELA EPN), monitored tumor growth via IVIS and randomized the mice into four groups (vehicle, BGB-290, Irinotecan and Irinotecan+Pamiparib) when a predefined threshold of tumor growth was reached. Mice were treated with Irinotecan (or vehicle) once per day i.p. and Pamiparib (or vehicle) twice per day per oral gavage. Treatment with Pamiparib did not show any survival benefit, but mice treated with Irinotecan or the combination showed a clear survival benefit. Treatments are ongoing and more results will be presented at the conference.